Study on distribution and relative abundance of click beetle pests (Elateridae: Agriotes sp.) in Hungarian maize fields - Nagy, Antal; Szarukán, István; Lovász, Erzsébet; Dávid, István (Acta Agraria Debreceniensis, 2011)
Click beetle pests (Elateridae: Agriotes sp.) of 24 sites in different regions of Hungary were studied in 2011. A. brevis, A. sputator, A.obscurus, A. lineatus, A. rufipalpis and A. ustulatus were sampled by pheromone traps in maize fields. During the study 65895 beetles werecaught. A. ustulatus and A. sputator were the most abundant species. Beyond that 23 additional species were trapped so the total number of sampled species was 29. The distribution of the six studied species was uneven. In east Hungary A. ustulatus were the most abundant, whilein the Transdanubia A. sputator was dominant in the most studied sites. A. obscurus occurred mostly in Transdanubia (western Hungary), and it occurred only in one site of eastern Hungary. The abundance of one or simultaneously two species reached the threshold of significant damage in 14 sites. Additionally there were three sites where the total abundance of the two most dominant species reached the threshold. There were only six sites where we should not expect significant damage. In this reason we have to monitor the populations of these pests and if it is necessary we have to take actions against them.